Determination of the physiological races of fusarium oxysporum f.sp. dianthi on carnation in colombia (1991)
One of the most limitting problemsof the carnation crop in Colombia is the vascular wilt caused by the fungus Fusarium oxysporum f. sp. dianthi. This work was done to determine the morphological, cultural, reproductive and pathological variability of 121 isolates collected from 61 farms located at the Bogotá Plateau. Nine foreing isolates of the races 1,2.4 and 8 were also used as control. The pathogenicity tests were done by inoculation of rooted cuttingsin six differential varieties. All isolates had aradial rate of growth close to one centimeterper day. The colonies showed great variabilityin mycelial color, apparence and produetion of spores. All 130 insolates of the fungus were pathogenic to one or more of the diffeferences in incubation period, plant colonization and symptoms. One hundred and twelve isolates were identify as Race 2 of the pathogen based on their reaction of resistancein Ibiza and Niki, and their reaction of susceptibility in Pink Calypso, Raggio di Soleand San Remo. Saven isolates could not be identified with in the known races, according to its low level of pathogenicity and aninconsistent reaction in the differential varieties. We found four different reactions in Taiga, which is supposed to be resistant toall know races: Resistant (30%), Moderately Resistant (34%), Moderately Susceptible (21%) and Susceptible (15%). For these reactions we suggest the presence of four variants of Race 2 of the pathogen. These reactions could explain the variable behavior of some varieties in Colombia.